2004
DOI: 10.1111/j.1468-0262.2004.00550.x
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Likelihood-Based Inference in Conditional Moment Restriction Models

Abstract: This paper proposes an asymptotically efficient method for estimating models with conditional moment restrictions. Our estimator generalizes the maximum empirical likelihood estimator (MELE) of Qin and Lawless (1994). Using a kernel smoothing method, we efficiently incorporate the information implied by the conditional moment restrictions into our empirical likelihood-based procedure. This yields a one-step estimator which avoids estimating optimal instruments. Our likelihood ratio-type statistic for parametri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
166
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(169 citation statements)
references
References 38 publications
3
166
0
Order By: Relevance
“…Testing is considered in Kitamura (2001) for moments restrictions, and Tripathi and Kitamura (2002) for conditional moment restrictions. Estimation and testing with conditional moment restrictions are studied in Donald, Imbens and Newey (2003) and Kitamura, Tripathi and Ahn (2002). They found that EL posses the attractive features of avoiding estimating optimal instruments and achieving asymptotic pivotalness.…”
Section: Introductionmentioning
confidence: 99%
“…Testing is considered in Kitamura (2001) for moments restrictions, and Tripathi and Kitamura (2002) for conditional moment restrictions. Estimation and testing with conditional moment restrictions are studied in Donald, Imbens and Newey (2003) and Kitamura, Tripathi and Ahn (2002). They found that EL posses the attractive features of avoiding estimating optimal instruments and achieving asymptotic pivotalness.…”
Section: Introductionmentioning
confidence: 99%
“…When the moment function a is finitely parameterized, the conditional density projections correspond to the population counterpart of the objective function of semiparametric efficient estimator (Kitamura et al, 2004). Having sufficient conditions for the existence of the limit of the objective is the building step to study the properties of these estimators under misspecification.…”
Section: Discussionmentioning
confidence: 99%
“…Section A.2 contains the consistency proof. By and large, we follow the structure of the proofs in Kitamura, Tripathi, and Ahn (2004) and Newey and Smith (2004), making the necessary adjustments for the presence of the inequality moment conditions. In Section A.3 the quadratic approximation of the objective function is obtained.…”
Section: A Appendix: Proofs and Derivationsmentioning
confidence: 99%